On solid ground science, technology and integrated land management ([Ottawa, Ont., Canada] IDRC ; [S.l.] UNCTAD, 1997)
On Solid Ground describes how the tools of science and technology can be used to find solutions to global land management problems. The key is "integrated land management", which draws on the knowledge derived from the physical and social sciences and blends it with the wisdom of local communities, indigenous peoples, women, and others whose survival strategies have been based on a close connection to their mother Earth.
Foreword; Preface; Acknowledgments; Introduction. The Need for Science and Technology in Land Management; Chapter 1. Challenges and Opportunities for Integrated Land Management; Chapter 2. Contributions of Science and Technology to Integrated Land Man agement; Chapter 3. Constraints on Integrated Land Management; Chapter 4. Conclusions and Recommendations: Approaches to Technology Transfer and Capacity-building; Appendix 1. The Panel on Integrated Land Management; Appendix 2. Applying Science and Technology in Integrated Land Management; Appendix 3. Acronyms and Abbreviations
Published on the International Development Research Centre website.
Title from Web page (IDRC, viewed June 27, 2006).
Includes bibliographical references.
Online version of the print publication.
Mode of access: World Wide Web.
Keywords: Land use -- Management; Land use -- Planning; Sustainable development